2018
DOI: 10.1101/390377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in fear regulation and reward seeking behaviors in a fear-safety-reward discrimination task

Abstract: Reward availability and the potential for danger or safety potently regulates emotion. Despite women being more likely than men to develop emotion dysregulation disorders, there are comparatively few studies investigating fear, safety and reward regulation in females. Here, we show that female Long Evans rats do not suppress conditioned freezing in the presence of a safety cue, nor do they extinguish their freezing response, whereas males do both. Females were also more reward responsive during the reward cue … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…If not freezing, conditioned suppression, or nose poke cessation then perhaps another measure of fear? Danger cues elicit active fear responses: escape-like behaviors such as darting (Greiner et al, 2018; Gruene et al, 2015). However, darting is prevalent in females, but less so in males.…”
Section: Discussionmentioning
confidence: 99%
“…If not freezing, conditioned suppression, or nose poke cessation then perhaps another measure of fear? Danger cues elicit active fear responses: escape-like behaviors such as darting (Greiner et al, 2018; Gruene et al, 2015). However, darting is prevalent in females, but less so in males.…”
Section: Discussionmentioning
confidence: 99%
“…Despite there being evidence that sex differences may contribute to how animals engage with and process rewarding stimuli, sex is an often overlooked component when determining how an animal's internal state modulates reward-related behaviors. In fact, recent studies have shown that male and female mice exhibit divergent learning and decision-making strategies in reward-guided behaviors 20,41,42 . Moreover, sex differences in mPFC reward representations were shown to underlie some of the behavioral differences observed in nonsocial reward-seeking 43 .…”
Section: Introductionmentioning
confidence: 99%